2017
DOI: 10.1371/journal.pone.0169307
|View full text |Cite
|
Sign up to set email alerts
|

Defining Surrogate Endpoints for Clinical Trials in Severe Falciparum Malaria

Abstract: BackgroundClinical trials in severe falciparum malaria require a large sample size to detect clinically meaningful differences in mortality. This means few interventions can be evaluated at any time. Using a validated surrogate endpoint for mortality would provide a useful alternative allowing a smaller sample size. Here we evaluate changes in coma score and plasma lactate as surrogate endpoints for mortality in severe falciparum malaria.MethodsThree datasets of clinical studies in severe malaria were re-evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…A recent meta-analysis [ 25 ] and a large systematic review [ 17 ] of acutely ill adults have reported a consistent lower mortality associated with LC, not limited to septic patients and regardless of the initial lactate value. Also, a recent secondary analysis of two large clinical trials on antimalarials has shown that lack of LC is an independent predictor of death in adults with severe malaria [ 26 ]. Amongst the few paediatric studies published, Krishna and colleagues measured serial lactate concentrations during 24 h in a small cohort of 115 children with severe malaria in the Gambia, concluding that sustained HL was the most powerful prognostic indicator of fatal outcome [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis [ 25 ] and a large systematic review [ 17 ] of acutely ill adults have reported a consistent lower mortality associated with LC, not limited to septic patients and regardless of the initial lactate value. Also, a recent secondary analysis of two large clinical trials on antimalarials has shown that lack of LC is an independent predictor of death in adults with severe malaria [ 26 ]. Amongst the few paediatric studies published, Krishna and colleagues measured serial lactate concentrations during 24 h in a small cohort of 115 children with severe malaria in the Gambia, concluding that sustained HL was the most powerful prognostic indicator of fatal outcome [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to demonstrate an association between LC and survival in severely ill febrile children in a malaria-endemic area is relevant at least in two aspects. On one hand, LC could serve as a valid surrogate endpoint of clinical trials of malaria aiming to improve mortality, as recently demonstrated by Jeeyapant et al in a large cohort of adult patients with malaria [ 26 ]. Thus, one could hypothesise that LC might help to guide the initial resuscitation of these children in a resource-poor setting, where invasive monitoring and intensive care is mostly unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, new compounds with rapid activity against asexual blood stage parasites, suitable for parenteral administration, are needed for this critical indication (see TCP-1 specific attributes in [ 110 ]). The decline in the incidence of severe malaria in adults will require alternative development approaches, including the development of surrogate end points [ 115 ], as not enough patients will be available for large mortality studies [ 116 ]. However, sufficient safety data in adults would still be required for a phase III trial in African children with severe malaria.…”
Section: Drug Research Agendamentioning
confidence: 99%
“…General declines of malaria and SM burden, decreases in the CFR for malaria and difficulties in detecting reductions in mortality rates may hinder the evaluation of those interventions due to the need of recruiting large numbers of patients [ 29 ]. In this respect, it is necessary to creatively innovate in the design of clinical trials with more precise sample sizes, more accurate clinical predictors and surrogate endpoints for mortality like plasma lactate concentration [ 29 31 ]. It is recommended that patients with SM with signs of serious bacterial infection receive intravenous antibiotics [ 5 ].…”
Section: Introductionmentioning
confidence: 99%